PENGEMBANGAN KOMPETENSI JABATAN FUNGSIONAL PADA PUSAT PENGEMBANGAN SUMBER DAYA MANUSIA KEMENTERIAN DALAM NEGERI REGIONAL YOGYAKARTA - Mudji Estiningsih (LPSDI Bina Patria, 2024)
This research aims to determine the challenges faced by the Yogyakarta Regional Ministry of Home Affairs PPSDM after the publication of Permenpan RB No. 42 of 2018 concerning the Appointment of Civil Servants in Functional Positions Through Adjustments/Inpassing and Permenpan RB No. 7 of 2022 concerning Work Systems in Government Agencies to Simplify Bureaucracy states In carrying out their duties, Functional Officers and implementers can work individually and/or in work teams by prioritizing professionalism, as a new spirit in developing human resources to support the realization of Agile Human Resources. The research method used is descriptive qualitative, with a scalpel using the Training Need Analysis Tool, to be able to meet the availability of employees in the competencies required by the organization. The benefits of this research are to realize the development of HR Competencies in determining the availability of organizational needs with employee competencies as well as arranging levels of employee competency development and creating design models that are used as guidelines for carrying out HR development to fulfill certain functional positions.